Effect of Chemical Composition of Irrigation Water on Some Growth and Yield of Corn and P-availability in Calcareous Soil - Esmail, Akram Othman; Rajab, Kazhin Sarbaz (Sulaimani Journal for Pure and Applied Sciences, 2018)
The study was conducted during growing season of 2016, to study the effect of five water qualities (W) having the same electrical conductivity but differing in chemical composition (one of them natural water the others are artificial) and three levels of phosphorus fertilizer (P) on growth of corn and p-availability using factorial experiment based on completely randomized design (CRD) with 4 replicates. The results indicated that the water qualities, levels of applied P and their interactions affected significantly on dry weight and chlorophyll content and P concentration in both plant leaves and soil. The highest values of dry matter (146.13 , 138.32 and 151.501) g pot -1 were recorded from W2, P2 and W2P1. The highest values of chlorophyll content (40.85, 37.02 and 41.56) SPAD were obtained from W2, P1 and W2P1 respectively. On the other hand, the highest phosphorus concentration (0.68, 0.54 and 0.83) mg g-1 of dry matter were obtained from W2, P 2 and W2P2 respectively.
Keywords: Ratio between cations; P availability; Water quality; Corn